High-performance electronic transport in the plane of 3D type-II Dirac semimetals. (4th September 2017) - Ge, Yanfeng; Wan, Wenhui; Liu, Yong; Zhang, Ying
Abstract: Recently, the type-II Dirac fermion, a new topological state, has been proposed in the Al3 V family. It breaks Lorentz symmetry and has unique physical properties. We use first-principles calculations to investigate electronic transport limited by phonon scattering. The electronic resistivity in the xy plane is estimated to be 24.1 μ Ω ⋅ cm for Al3 V and is much lower than that along the z direction. The heavy electronic effective mass along the z direction and the main electron–phonon coupling, originating from the phonon modes vibrating along the z direction, lead to anisotropic electronic transport, which is also found in other members of the Al3 V family.